ONLINE CONSULTATION APPLICATION AT THE WOMEN AND CHILDREN PROTECTION UNIT OF THE INDRAGIRI HILIR RESORT POLICE STATION - Pane, Eddis Syahputra; Novendra, Rizki; Afriansyah, Afriansyah; Bunda, Yola Permata; Djusar, Syahtriatna (Universitas Lancang Kuning, 2024)
This study aims to determine the role of the Protection of Women and Childre in dealing with children in legal cases in the jurisdiction of the Indragiri Hilir Resort Police Station. The form of online counseling services is an alternative problem solving that makes it easier for people to consult regarding problems within the family. Online counseling services are also a place to respond to any complaints, protect and facilitate the handling of complaints submitted by victims and the public, where the privacy of victims and suspects will be protected according to their rights. The research uses waterfall analysis modeling using UML (Unified Modeling Language). This system is made using the PHP programming language, MySQL database. The designed application works in accordance with the system design mechanism at the beginning of the research object. The final result of this research is an online consultation application, where on this website the public can fill out a consultation form directly and view information that is directly related to counselors, the Legal Aid Institute, psychologists and therapists from the Women's and Children's Protection Unit Indragiri Hilir Resort Police Station